2010
DOI: 10.1016/j.biopsych.2009.09.032
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Thickness Is Influenced by Regionally Specific Genetic Factors

Abstract: Background Although global brain structure is highly heritable, there is still variability in the magnitude of genetic influences on the size of specific regions. Yet, little is known about the patterning of those genetic influences, i.e., whether the same genes influence structure throughout the brain or whether there are regionally-specific sets of genes. Methods We mapped the heritability of cortical thickness throughout the brain using 3D structural magnetic resonance imaging in 404 middle-aged male twin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
101
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 129 publications
(115 citation statements)
references
References 41 publications
12
101
1
1
Order By: Relevance
“…These regions are known to be structurally and functionally connected. This result is consistent with our previous report based on a limited seed-point analysis, which showed that the pattern of genetic correlations for cortical thickness partially correspond to neuroanatomical connectivity, with high genetic correlations between distal, noncontiguous regions (28). The cross-regional genetic patterning of cortical thickness may relate to underlying fiber tract structures (e.g., thalamocortical or intracortical connections).…”
Section: Discussion Genetic Influences On Cortical Thickness Showed Asupporting
confidence: 82%
See 1 more Smart Citation
“…These regions are known to be structurally and functionally connected. This result is consistent with our previous report based on a limited seed-point analysis, which showed that the pattern of genetic correlations for cortical thickness partially correspond to neuroanatomical connectivity, with high genetic correlations between distal, noncontiguous regions (28). The cross-regional genetic patterning of cortical thickness may relate to underlying fiber tract structures (e.g., thalamocortical or intracortical connections).…”
Section: Discussion Genetic Influences On Cortical Thickness Showed Asupporting
confidence: 82%
“…Magnetic resonance (MR) images do not have sufficient spatial resolution to examine cortical thickness by each layer; instead, we measure the combined thickness across all cortical layers at each cortical location. We have previously explored the genetic patterning of cortical thickness based on three preselected cortical locations (seed points), and findings suggested that the genetic correlation pattern of cortical thickness differs from that of surface area, lacking the A-P or lobar divisions observed in the latter (28). This limited seed-point analysis made no attempt to define gradients or discover specific genetic boundaries, however.…”
Section: Significancementioning
confidence: 99%
“…Such networks of anatomical change ("maturational coupling") are conjectured to 40 arise from the expression of common genetic cues during early development of the cortex (Raznahan et al, 2011). Supporting this are twin studies implicating genetics and structure (Schmitt et al, 2008;Rimol et al, 2010;Docherty et al, 2015), with one by Schmitt et al (2008) suggesting that the small-world network organization of structural covariance (He et al, 2007) might be explained by genetic correlations that display a similar pattern.…”
mentioning
confidence: 51%
“…A possible explanation for these findings might be associated with the distinct genetic influences that control CT and SA in the human cortex [Panizzon et al, 2009;Rimol et al, 2010;Winkler et al, 2010]. Chen et al [2012Chen et al [ , 2013 compared brain development in neurotypical monozygotic and dizygotic twins to test the effect of genetic factors on SA and CT.…”
Section: Discussionmentioning
confidence: 98%